A Review on the Fundamental Aspects of Female-Friendly Prayer Areas in Shopping Centres - Siti Ayeshah Shahrin; Haji Abdul Hafidz Omar (Al-Misbah (Jurnal Islamic Studies), 2022)
Performing the five-time prayer is an obligation for every Muslim, no matter where they are. The provision of prayer rooms in commercial buildings is one of the facilities offered by building managers to accommodate Muslim buyers in most Muslim countries. However, the muṣallá provided is often remote, placed in a small or poorly planned space that most users, especially women, will feel uncomfortable and uncomfortable. This article aims to identify the feasibility of places of worship facilities for women in malls. The method in this study is qualitative with a descriptive-analytical approach. The results showed that the problems that came to the fore included the unresponsiveness of prayer rooms for the needs of women, inadequate entrance locations, uncomfortable ablution places, not being equipped with the necessary facilities, and some even not being child-friendly for parents. From this literature search, several research recommendations to investigate features and facilities in prayer rooms to make the area more responsive to the needs of Muslim female buyers. The results of this research have contributed to the development of Islamic education, namely increasing mutual awareness about the importance of providing decent worship facilities, especially for women.